Análise sensorial de carne bovina com cobertura de quitosana e extratos naturais - Nobre, Elaine Cristine Alves Soares (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this research was to evaluate the use of edible chitosan coatings added with natural extracts as preservatives of beef and their influence on sensory characteristics. At first filmogenic mixtures containing 3% chitosan were prepared, in addition to 8%, 6% and 8% of the extracts of rosemary, onion and urucum, respectively, the meat samples were immersed in the filmogenic mixtures and analyzed later, the analyzes performed were: physical (pH, color, water retention capacity, cooking weight loss and shear force), microbiological (detection of Salmonella spp.), antioxidant activity (TBARS), sensory analysis. The results of the physical analyzes show that there was no significant effect (p <0.05) between the treatments for pH. The highest water retention capacity was found in 6% onion extract and 8% rosemary toppings. The weight loss in the cooking of the samples containing the extracts was smaller than in the control samples and containing chitosan. Shear force also showed differences between treatments, all samples had a decrease in shear force. In microbiological analyzes, the absence of Salmonella spp. in 25g of sample. All toppings showed significant antioxidant capacity between treatments. The results of the sensory analysis show that there was no significant effect (p <0.05) between the treatments, however, the cover containing the annatto extract obtained a higher average for the evaluated attributes. Thus, it is concluded that the coverings based on chitosan and natural extract had influence on the conservation and quality of beef, having good acceptance among consumers mainly the meat containing urucum extracts coverage more accepted by the tasters.
Keywords: Aditivos alimentares; filmes comestíveis; segurança alimentar; Food additives; edible films; food safety; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL